PARKINSON'S DISEASE IN PATIENTS WITH HIV INFECTION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article presents a literature review of cognitive impairment in Parkinson's disease in HIV-infected patients. Pathogenetic intersections between HIV-associated neurocognitive disorders (HAND) and Parkinsonism are analyzed. Neurodegeneration, with an emphasis on the role of the dopaminergic system, chronic neuroinflammation, and basal ganglia damage. This article describes the clinical and neuropsychological features of cognitive deficits associated with Parkinson's disease and HIV infection, along with data from modern neuroimaging and biomarker studies, as well as the impact of antiretroviral therapy and dopaminergic treatment on cognitive prognosis. The need for early cognitive screening and a multidisciplinary approach to managing this patient population is emphasized.